2023
DOI: 10.1111/pbr.13123
|View full text |Cite
|
Sign up to set email alerts
|

Status of yam (Dioscorea spp.) in the Democratic Republic of Congo

Abstract: Yam is an important tuber crop with enormous potential to enhance rural sustenance and livelihood in DRC. However, studies to enhance its genetic improvement are very far from sufficient with only a handful of information available on the crop. Yam has been treated as an orphan crop compared to contemporary crops such as cassava and sweet potato which have adapted to different cropping systems and become widespread in production. The lack of research attention to address the major production challenges has fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In this way, yam farming is key for food security as it diversifies food and income of rural households in eastern DRC. These results agree with those of Adejumobi et al (2022bAdejumobi et al ( , 2023 in northwestern DRC that showed that yam is, in surface and volume, a secondary crop and is mainly on house gardens and small farmlands (<0.25 ha), using traditional farming methods and local landraces. Previous reports listed yam among neglected and underutilized (orphan) crop species in DRC (Mondo et al, 2021;Adejumobi et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this way, yam farming is key for food security as it diversifies food and income of rural households in eastern DRC. These results agree with those of Adejumobi et al (2022bAdejumobi et al ( , 2023 in northwestern DRC that showed that yam is, in surface and volume, a secondary crop and is mainly on house gardens and small farmlands (<0.25 ha), using traditional farming methods and local landraces. Previous reports listed yam among neglected and underutilized (orphan) crop species in DRC (Mondo et al, 2021;Adejumobi et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…Seed access depended largely on seed exchanges among farmers or purchased from informal markets. Since yam diversity is high in DRC (Magwé-Tindo et al, 2018), farmers were also acquiring seeds from forest environments, a practice referred to as ennoblement elsewhere (Scarcelli et al, 2006;Chikwendu and Okezie, 2014;Agre et al, 2021;Adejumobi et al, 2023). In addition to poor farming practices and informal seed system, farmers lacked sufficient knowledge of tuber storage techniques and value addition, leading to high post-harvest losses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations